Seed nutrient content rather than size influences seed dispersal by scatterhoarding rodents in a West African montane forest. (14th July 2020) - Yadok, Biplang G.; Forget, Pierre-Michel; Gerhard, Daniel; Aliyu, Babale; Chapman, Hazel
Abstract: Rodents can be important in seed dispersal through their scatterhoarding behaviour, yet, the seed traits that are most influential in seed removal by Afrotropical scatterhoarding rodents remains unclear. Here, we investigated the effect of seed size and nutrient content of four seed species on the scatterhoarding behaviour of rodents in an Afromontane forest, Ngel Nyaki forest, Nigeria. To do this we marked with thread-tags the seeds of Santiria trimera, Beilschmedia mannii, Carapa oreophila and Anthonotha noldeae and observed their fate. We predicted that (1) caching frequency would be higher for larger than smaller seed species; (2) caching frequency would be higher for nutrient-rich than nutrient-poor seeds; (3) larger seeds would be taken across farther distances; and (4) survival of cached seeds would be higher for nutrient-rich seeds. In contrast to studies elsewhere we found no difference in caching probabilities based on seed size, although nutrient-rich (high fat content) seeds had a higher probability of being predated than seeds with lower fat content. Larger and smaller seeds were dispersed over the same distances and nutrient-poor (high fibre content) seeds survived longer in seed caches. Overall, our findings suggest that large, nutrient-rich seed species are less likely to be dispersed by rodents.